2018
DOI: 10.1002/chem.201800900
|View full text |Cite
|
Sign up to set email alerts
|

Accurate pH Sensing using Hyperpolarized 129Xe NMR Spectroscopy

Abstract: In the search for powerful non-invasive methods for pH measurement, NMR usually suffers from biases, especially for heterogeneous samples or tissues. In this Communication, using the signals of hyperpolarized Xe encapsulated in a pair of water-soluble cryptophanes, we show that a differential pH measurement can be achieved, free from most of these biases, by monitoring the difference between their chemical shifts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 18 publications
0
28
1
Order By: Relevance
“…51 Berthault et al demonstrated how the NMR chemical shi of 129 Xe encapsulated by a hexa-carboxylate-functionalized cryptophane is highly pH dependent, 52 and later used the chemical shi difference of encapsulated 129 Xe in two different cryptophanes for more precise pH measurement. 53 Finally, Yang et al designed a cryptophane functionalized with a thiol-reactive acrylate moiety, which allowed for the detection of, and differentiation between biothiols such as cysteine, homocysteine, and glutathione. 54 These innovative examples of cryptophanebased biosensor design highlight where recognition moieties can be tailored for highly specic and selective binding.…”
Section: Direct Detection Of Cryptophane-encapsulated 129 Xementioning
confidence: 99%
“…51 Berthault et al demonstrated how the NMR chemical shi of 129 Xe encapsulated by a hexa-carboxylate-functionalized cryptophane is highly pH dependent, 52 and later used the chemical shi difference of encapsulated 129 Xe in two different cryptophanes for more precise pH measurement. 53 Finally, Yang et al designed a cryptophane functionalized with a thiol-reactive acrylate moiety, which allowed for the detection of, and differentiation between biothiols such as cysteine, homocysteine, and glutathione. 54 These innovative examples of cryptophanebased biosensor design highlight where recognition moieties can be tailored for highly specic and selective binding.…”
Section: Direct Detection Of Cryptophane-encapsulated 129 Xementioning
confidence: 99%
“…It is noteworthy that compound 3 has recently been used as a pH sensor in combination with laser-polarized xenon NMR. 47 Two different strategies were tested to prepare cryptophane 3: the synthetic pathway 1, named the two-step approach, requires the use of two different protecting groups to protect both the phenol and the ester functions. In contrast, the synthetic pathway 2, named the one-step approach, uses the same protecting groups for both chemical functions.…”
Section: Synthesis Of Compoundmentioning
confidence: 99%
“…In cryptophane 1 the two cyclotriver- Xenon inside these cage-molecules resonates at 52 ppm (for Xe@1) and 42 ppm (for Xe@2) if one calibrates the signal of xenon free in water at 196 ppm. These two molecular systems could be used as probes for pH, as the chemical shift of caged xenon varies as a function of the concentration in H + ions (Léonce et al, 2018 Chauvin et al (2016). BE: Beam Expander; BS: polarization Beam Splitter cube; MI: mirror; λ/4: quarterwave plates; PW: Powermeter.…”
Section: Molecular Systemsmentioning
confidence: 99%
“…The approach of 129 Xe NMR-based biosensing using functionalized cryptophanes has yet been successfully applied in vitro for detection of small analytes (Tassali et al, 2014;Dubost et al, 2014;Jeong et al, 2015;Yang et al, 2016;Guo et al, 2016;Yang et al, 2017), of large biosystems (Wei et al, 2006;Chambers et al, 2009;Boutin et al, 2011;Rose et al, 2014;Taratula et al, 2015;Khan et al, 2015;Riggle et al, 2017;Milanole et al, 2017;Schnurr et al, 2020), or of change of physiological conditions: temperature (Schröder et al, 2008;Schilling et al, 2010) or pH (Léonce et al, 2018). To date, it has however never been used in vivo; only a proof of concept has been performed on rats using a non-functionalized cucurbituril (Hane et al, 2017).…”
Section: Introductionmentioning
confidence: 99%